Minor Languages of Mindoro - Postma, Anton (The Archive, 2025)
Talking about the “Minor Languages of Mindoro” might come as a surprise to someone who knows that Mindoro Island, with its two provinces, Oriental & Occidental, belong to REGION IV, or the Southern Tagalog Region, alongside Batangas, Laguna and neighboring Tagalog speaking provinces. So why then talk about Mindoro’s “Minor Languages”? [...] When I received the kind invitation of Dr. Ernesto Constantino and Prof. Anicia Del Corro to present a talk about the Minor Languages of Mindoro, it was clear to me that they meant the languages spoken by Mindoro’s 40,000 or so original inhabitants, generally known as the Mangyans. Less generally, however, is it known that these so called Mangyans, are easily distinguished into a number of separate ethno-linguistic groups, based on their different languages, customs and cultural expressions.